2008
DOI: 10.1016/j.chemosphere.2007.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectroscopic characterization of DOM fractions isolated from a filtered river water after ozonation and catalytic ozonation

Abstract: Fluorescence spectra were applied to investigate the structural changes of four dominant dissolved natural organic matter (DOM) fractions of a filtered river water before and after ozonation and catalytic ozonation. The ozonation and catalytic ozonation with synthetic goethite (FeOOH) and cerium dioxide (CeO 2 ) were carried out under normal conditions, i.e. pH 7, reaction time of 10 min, and ozone/DOC ratio of about 1. The fluorescence spectra were recorded at both excitation-emission matrix (EEM) and synchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(39 citation statements)
references
References 40 publications
2
31
0
6
Order By: Relevance
“…Various studies revealed that the fluorescence upon oxidation depends on the nature of NOM and ozone dosage. Similarly to our results, Zhang et al (2008) also reported a reduction of the intensity at λ 280, 380, and 460 nm in river water during oxidative processes indicative of significant destruction of aromatic structures associated with generation of carbohydrates. Rodríguez et al (2014b) reported that humic acids presented an increase in fluorescence at low to moderate dosage of ozone, whereas fulvic acids showed a reduction in fluorescence regardless the ozone applied.…”
Section: Synchronous Fluorescence Spectroscopysupporting
confidence: 87%
See 2 more Smart Citations
“…Various studies revealed that the fluorescence upon oxidation depends on the nature of NOM and ozone dosage. Similarly to our results, Zhang et al (2008) also reported a reduction of the intensity at λ 280, 380, and 460 nm in river water during oxidative processes indicative of significant destruction of aromatic structures associated with generation of carbohydrates. Rodríguez et al (2014b) reported that humic acids presented an increase in fluorescence at low to moderate dosage of ozone, whereas fulvic acids showed a reduction in fluorescence regardless the ozone applied.…”
Section: Synchronous Fluorescence Spectroscopysupporting
confidence: 87%
“…The third peak at λ em ∼330 nm, which has the highest intensity, represents more complex structures, such as substituted aromatic rings and compounds of higher MW. At λ em ∼465 nm, a shoulder peak, which corresponds to high MW humic materials and aromatic structures with high degree of conjugation, can be seen (Chen et al 2003;Duarte et al 2003;Fu et al 2007;Peuravuori et al 2002;Santos et al 2010;Sierra et al 2005;Zhang et al 2008). Raw water exhibited different fluorescence intensities during different sampling campaigns (Fig.…”
Section: Synchronous Fluorescence Spectroscopymentioning
confidence: 92%
See 1 more Smart Citation
“…The positions, shifts, and intensities of the fluorescence peaks provide information not only on conformational changes but also on intramolecular and intermolecular interactions (Mobed et al 1996;Chen et al 2003a;Zhang et al 2008). As shown in Fig.…”
Section: 3 Conformational Changes In Dom Moleculesmentioning
confidence: 97%
“…The intensities of Zone 3 and 4 (270 -280 nm excitation) fluorophores (tyrosine-like and tryptophan-like compounds respectively) was also found to decrease during 30 days of aerobic biodegradation. This reduction can be attributed to the breakdown of proteineous materials by aeration (Zhang et al, 2008). Fig.…”
Section: Fluorescence Spectroscopic Resultsmentioning
confidence: 99%